2020
DOI: 10.21203/rs.3.rs-26945/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA GAS5 suppresses the proliferation and invasion of osteosarcoma cells via the miR-23a-3p/PTEN/PI3K/AKT pathway

Abstract: Background: Accumulating evidence has shown that lncRNA growth arrest special 5 (GAS5) is a well‑known tumor suppressor in the pathogenesis of a variety of human cancers. However, the detailed role of GAS5 in osteosarcoma is largely unclear. Here, we explore the role of GAS5 in progression of osteosarcoma. Methods: The expression level of GAS5 was detected in human osteosarcoma tissues and matched adjacent tissues, as well as osteosarcoma cell lines and non-malignant osteoblast cells. Then, in vitro gain- and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Among many anticancer drugs, MMP-9 is an extracellular matrix degrading enzyme highly expressed in various tumor tissues. MMP-9 exerts its biological function by degrading various extracellular matrix components and adhesion molecules [6][7] . Studies have shown that Mki67 inhibitor inhibits cell proliferation, migration, and invasion by inhibiting MMP-9 activity [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…Among many anticancer drugs, MMP-9 is an extracellular matrix degrading enzyme highly expressed in various tumor tissues. MMP-9 exerts its biological function by degrading various extracellular matrix components and adhesion molecules [6][7] . Studies have shown that Mki67 inhibitor inhibits cell proliferation, migration, and invasion by inhibiting MMP-9 activity [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%